Influence of Y-substitution on phase composition and proton uptake of self-generated Ba(Ce, Fe)O3−δ–Ba(Fe, Ce)O3−δ composites. Issue 5 (24th November 2021) - Berger, Christian; Bucher, Edith; Merkle, Rotraut; Nader, Christina; Lammer, Judith; Grogger, Werner; Maier, Joachim; Sitte, Werner
Abstract : Substitution with Y affects phase formation and the local cation stoichiometry of the Ce-rich and Fe-rich phases of BaCe1−( x + z ) Fe x Y z O3− δ self-generated composites. This is of particular importance for the water uptake in these compounds. Abstract : Self-generated composites from the series BaCe1−( x + z ) Fe x Y z O3− δ with z = 0.2 for 0.1 ≤ x ≤ 0.6 and z = 0 for Ce : Fe = 1 were obtained by one-pot synthesis. The composites consist of proton and electron conducting phases and are interesting as electrode materials for protonic ceramic fuel and electrolyser cells. X-ray diffraction with quantitative phase analysis and scanning electron microscopy with energy-dispersive X-ray spectroscopy showed that the materials consist of Fe-rich phases and a Ce-rich perovskite phase, which are present in the corresponding proportion depending on the precursor composition (Ce–Fe ratio). Substitution with Y leads to a narrowing of the miscibility gap compared to BaCe1− x Fe x O3− δ composites, thus favouring transformation of the composites into single cubic phases at temperatures above 1000 °C. Further, Y influences the mutual solubility of Fe 3+/4+ and Ce 4+ in the Ce-rich and Fe-rich phase, respectively, as shown elemental mapping via scanning transmission electron microscopy. As only a small proportion of the Y dissolves in the electrolyte-type phase, the increased proton uptake resulting from the incorporation of Y in the Ce-rich phase is limited. Strategies to overcome this limitation by substitution with ions with similar ionic radii, but different basicity, are discussed.